Does perceived cultural discrimination influence immigrants’ perceptions of the police?: evidence from married immigrant women living in South Korea - Choi, Jaeyong (Crime & delinquency, 2022)
Although policing scholars have discussed possible relationships between discrimination and perceptions of the police, assessing the impact of perceived cultural discrimination on perceptions of the police among immigrants is virtually non-existent and deserving of empirical scrutiny. The current study addresses this gap in the literature by examining the effect of perceived cultural discrimination on perceptions of the police using a sample of 1,272 married immigrant women living in South Korea. Our results show that perceived cultural discrimination is negatively and significantly associated with perceptions of the police, supporting the expressive nature of perceptions of the police among immigrants.